Analisis Tasybih Dhimni Dalam Al-Qur’an Surah Al-A’raf Ayat 40 : (Tinjauan Balaghah Al-Qur’an) - Sarah Kumala Batubara; Lisa Nur Azizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article aims to analyze the verse about tasybih dhimni in the Al-Qur'an surah Al-A'raf verse 40. The author chose surah Al-A'raf verse 40 because there is a verse about tasybih dhimni. The method used in this article is qualitative, with a library research type of research. The library research method is to explain the material you want to discuss by collecting various data sources, namely from journals, theses, articles as data sources. In surah Al-A'raf verse 40 there is a sentence that is included in the tasybih dhimni, namely لَا تُفَتْحُ لَّهُمْ أَبْوَابُ السَّمَاء , where this sentence is the object or topic of the second sentence of the parable, namely حَتَّى يَلِجُ الْجَمَلُ فِي سَمِّ الخياط is different from other tasybih, the wording of this tasybih side by side. This type of tasybih shows that the meaning of what is based on the musyabbah is possible.